Listen! - Tolan, Stephanie S. (New York : HarperCollinsPublishers, 2006)
During her solitary convalescence from a crippling accident, twelve-year-old Charley finds a wild dog, and the arduous process of training him leads her to explore her feelings about her mother's death two years earlier.
Accelerated Reader AR
Keywords: Dogs; Friendships; Overcoming hard circumstances; Juvenile fiction